1024 THE IMPACT OF FRAILTY ON 30-DAY MORTALITY FOLLOWING PRIMARY HIP AND KNEE ARTHROPLASTY DUE TO OSTEOARTHRITIS. (14th June 2022) - Cook, M J; Lunt, M; Board, T; O'Neill, T W
Abstract: Introduction: We determined the association between frailty and 30-day mortality following total hip and knee arthroplasty (THA/TKA) due to osteoarthritis and also the impact of THA/TKA on 30-day mortality compared to a control population. Method: We used linked primary and secondary care data and Office for National Statistics mortality data. Frailty was assessed using the electronic frailty index and categorised as fit, mild, moderate, and severe frailty. The association between frailty and 30-day mortality following THA/TKA was assessed using Cox regression, adjusted for year of birth, sex, quintile of index of multiple deprivation and year of surgery. Mortality following THA/TKA was also compared to a control population who had osteoarthritis but no previous THA/TKA, matched on year of birth, sex, and quintile of index of multiple deprivation. Results: 103, 563 cases who had a THA, 125, 367 who had a TKA, and matched controls contributed data. Among those who had surgery, 30-day mortality increased with increasing frailty; adjusted hazard ratio (HR) (95% CI) among severely frail vs fit: following THA, 2.85 (1.84, 4.39); following TKA, 2.14 (1.29, 3.53). Compared to fit controls who did not have surgery, 30-day mortality was higher among fit people who had THA and TKA, respectively, adjusted HR 1.60 (1.15, 2.21) and 2.98 (1.81, 4.89). There was, however, no statistically significant difference in 30-day mortality among cases with mild, moderate and severe frailty compared to controls in the same frailty category. Conclusion: Among people who had THA and TKA, 30-day mortality increased with increasing frailty. A healthy surgery (selection) effect may have impacted on the comparison of mortality among cases who had THA/TKA and controls who did not have surgery.